WOMEN IN THE ELECTORAL POLITICS: A CASE STUDY OF 2016 SARAWAK STATE LEGISLATIVE ASSEMBLY ELECTION - Nadrawina, Isnin; Lucy, Sebli-Seidelson (2017)
This paper examines the women’s political participation as election candidates in Sarawak. The study will centre on the behind scenes of the 2013 General Election / GE13 (Sarawak Parliamentary seats). The investigation aims to contribute to the existing resource on women's political participation in Sarawak and Malaysia in general. The generated data may support the clamour for more participation of women as election candidates in Malaysian politics, particularly in Sarawak. The objectives are to produce a comprehensive gender ranking of political parties’ candidates list for 2013 election and to highlight issues pertaining to women's participation in this electoral politics. There is a record number of women (eight candidates) contested in GE13 for Sarawak constituency areas and five of the eight women candidates won their election. Further, some of the interesting features in this election are the ability of the winners to gain more votes from the male candidates which also indicated their popularity even though they were fielded for the first time (for example a female candidate from PBB). Thus, a candidate’s gender does not seem to be a major factor for voters in deciding when they decide whom to vote. It is also interesting to observe the battle between two big political parties that represents the Bumiputera (PBB) and the Chinese dominated party (DAP) continued to field the women candidates and eventually won with a big majority. The remaining PBB’s counterparts, SUPP and, PRS remains a status quo for not fielding any women candidates in the 2008 GE and the 10th State Election in 2011. On the other hand, SPDP stays staunch with the sole woman candidate since Sarawak State Election of 2006. With no women candidates in the said parties indicated the question of how serious are the political parties in pursuing women’s wish to their political participation in the government. Therefore, this study will aim or attempt to establish that it is evident that men still dominate the electoral candidatures in Sarawak.